Annulative π-extension of 1-phenylsulfonyl-2/3-bromomethylindole via Zn(OTf)2-mediated domino reaction with thiophene analogs. Issue 11 (18th June 2022) - Manikandan, Palani; Sankar, Elumalai; Mohanakrishnan, Arasambattu K.
Abstract: The reaction of isomeric 2/3-bromomethylindoles containing masked aldehydic function with heteroarenes in the presence of Zn(OTf)2 as a catalyst in 1, 2-DCE at room temperature led to the formation of benzo[ b ]-hetero annulated carbazoles. Graphical Abstract: UF0001